Formulasi Sediaan Eyebrow Cream Arang Aktif Batok Kelapa - Sertin Prilda Sari Sandoro; Suprianto Suprianto; Sumardi Sumardi (Journal of Indah Science and Clinic, 2021)
Eyebrow cream (EC) is one of the decorative cosmetics applied to the eyebrows using a brush for the purpose of giving color and emphasizing the shape of the eyebrows. EC is one of the practical preparations to fill in empty eyebrow hairs. The research was conducted of formulating activated charcoal into EC. The research method includes the formulation and evaluation of EC results from coconut shell activated charcoal at concentrations of activated charcoal 1%, 3%, 5% and 7%. Evaluation includes: organoleptic, homogeneity, irritation and pH of Eyebrow Cream. The organoleptic showed that the color of the preparation at a concentration of 1% -7% was black to dark black, with a cocoa oleum aroma, and a semi-solid texture. The pH of the preparation is 4.5-6.5 with good homogeneity. The preparation did not show irritation to the skin of volunteers. The study provide information that activated charcoal can be formulated into EC preparations. Coconut shell activated charcoal can be formulated in the form of eyebrow cream. The preparation of eyebrow cream does not cause irritation and is safe.